(Re)Setting Epigenetic Clocks: An Important Avenue Whereby Social Conditions Become Biologically Embedded across the Life Course. (September 2021) - Simons, Ronald L.; Lei, Man-Kit; Klopach, Eric; Berg, Mark; Zhang, Yue; Beach, Steven S. R.
Research on biological embedding of the social environment has been expedited by increased availability of biomarkers. Recently, this arsenal of measures has been expanded to include epigenetic clocks that indicate in years the extent to which an individual is older or younger than their chronological age. These measures of biological aging, especially GrimAge, are robust predictors of both illness and time to death. Importantly for sociologists, several studies have linked social conditions to these indices of aging. The present study extends this research using longitudinal data from a sample of 223 black women participating in the Family and Community Health Study. We find that changes in income and living arrangements over an 11-year period predict changes in speed of biological aging. These results provide further support for the idea that epigenetic aging is a mechanism whereby social conditions become biologically embedded. The utility of epigenetic clocks for sociological studies of health are discussed.